Organic Carbon Burial Following the Middle Eocene Climatic Optimum (MECO) a Mechanism for Global Cooling? - D. J. Spofforth; C. Agnini; H. Pälike; D. Rio; L. Lanci; E. Fornaciari; L. Giusberti; V. Luciani; G. Muttoni (2008)
Long-term cooling through the Eocene was interrupted ~40 Ma by a ~500 kyr long climatic warming event in the Middle Eocene known as the Middle Eocene Climatic Optimum (MECO). Here, we present coupled trace metal geochemistry and stable isotope data for the Alano di Piave section, NE Italy over the MECO interval. Originally documented at several deep sea sites in the Southern Ocean (Bohaty and Zachos, 2003), we confirm the widespread extent of MECO from a marginal basin in the western Teyths. The initiation of the isotope excursion, interpreted to be the MECO event, occurs within magnetochron C18r at ~40.5 Ma with minimum δ18O and δ13C values achieved at the base of C18n.2n ~40.13Ma, which are interpreted to represent peak warming conditions. Trace element geochemistry is coupled with bulk stable isotopes, δ18O, inorganic carbon (δ13Ccc) and organic carbon (δ13Corg), and both CaCO3 and organic carbon sediment content (TOC) to investigate this significant paleoenvironmental change following the MECO. Two organic rich intervals (up to 3% TOC) are associated with increases in the concentration of sulphur, and redox-sensitive trace metals, very low concentrations of Mn and the occurrence of pyrite. Together these changes imply low bottom water O2 conditions, possibly anoxic to dysoxic during this interval. At the same time nannofossil assemblages shift from oligotrophic to eutrophic suggesting increased nutrient input and surface ocean productivity. As do negative δ13Corg excursions and positive δ13Ccc excursions coincident with the organic rich intervals. Increases in terrigenous and organic marine matter to the sediment precede the first organic rich interval and may provide a driving mechanism for the development of anoxic conditions. Furthermore the rapid burial of organic carbon will have lowered global pCO2 and returned the climate system to the general Eocene cooling trend. Bohaty, S. M., & J. C. Zachos, (2003) Geology, 31, 1017-1020